Atypical Presentation and Management of Fibrodysplasia Ossificans Progressiva - Grenho, A (2017)
We report a case of an 18-year-old woman, with bilateral acute inflammatory pain on the hip area, during the premenstrual period, and progressive increase in volume and rigidity of both hips. Bilateral exuberant soft tissue calcifications were present on the radiographic exams, and the patient also presented with bilateral short-length hallux valgus. A heterozygous mutation in the protein kinase domain of ACVR1 gene was found, allowing the diagnosis of fibrodysplasia ossificans progressive. Due to the relation between the disease flares and the premenstrual period, the patient was put into a chemically induced amenorrhea, with no new inflammatory crises since.This case illustrates the importance of an accurate diagnosis to prevent unnecessary diagnostic procedures, as well as the need to develop specific treatment strategies to address each patient's particular needs.